The Influence of Teachers' Roles on Child-Friendly School Policies and Implementation in Kindergartens - Muslichah Tri Suprapti; Tri Joko Raharjo; Edi Waluyo (Universitas Pendidikan Ganesha, 2025)
Child-Friendly Schools (CFS) have yet to fully achieve their intended objectives, primarily due to several contributing factors such as the lack of coordination and collaboration among stakeholders and policy implementers, as well as limitations in human resources. The purpose of this study is to analyze the influence of teachers’ roles on the policies and implementation of child-friendly schools in kindergartens. This research adopts a quantitative approach. The population consists of 53 kindergarten teachers, and the sampling technique used is saturated sampling (census), resulting in a total sample of 53 teachers. Data were collected through questionnaires, with the research instrument in the form of structured survey sheets. The data analysis techniques employed include both descriptive and inferential statistics. The results of the study show that the role of teachers falls into the moderate category at 43.40%. Similarly, the child-friendly school policy and its implementation are also categorized as moderate, with scores of 43.40% and 54.71%, respectively. The partial test analysis (t-test) indicates a significant influence of teachers' roles on both the policies and implementation of child-friendly schools. The Unstandardized B coefficient confirms a measurable effect of teachers’ roles on child-friendly school policy and implementation. The Adjusted R-Square value for child-friendly school policy is 0.463, suggesting that 46.3% of the variance in policy is explained by the role of teachers, while the remaining 53.7% is attributed to other factors not examined in this study. Furthermore, the role of teachers accounts for 48.6% of the variance in the implementation of CFS, with 51.4% influenced by other unexamined components. The implication of this research is that the role of teachers has a significant impact on the implementation of child-friendly school practices, underscoring the need to strengthen teacher involvement and capacity in order to advance CFS initiatives effectively.